Polarized emission from GaN/AlN quantum dots subject to uniaxial thermal interfacial stresses - Moshe, O.; Rich, D. H.; Damilano, B.; Massies, J. (Journal of vacuum science and technology. B, Nanotechnology & microelectronics, 2010)
The authors have studied the excitation-dependent optical properties of GaN/AlN self-assembled quantum dots (QDs) grown on Si(111) substrates. Ensembles of QDs were subject to various external stress configurations that resulted from the thermal expansion coefficient mismatch between the GaN/AlN layers and the Si(111) substrate and ranged from in-plane uniaxial stress, primarily along the ⟨11-20⟩ directions, to in-plane biaxial stress, having magnitudes ranging from 15 to 30 kbars. The authors have exploited microcracks that form during the postgrowth cooling as stressors in order to create the highly localized regions of uniaxial stress over limited regions of the samples. Cathodoluminescence (CL) measurements of the excitonic transitions exhibit an in-plane linear polarization anisotropy in close proximity to microcracks that is strongly dependent on the e-beam current used to excite the QD ensemble. The excitonic transition energy in varying proximity to the microcracks was studied with CL wavelength imaging. Some aspects of the carrier recombination are inferred from the temperature dependence of the integrated CL intensity. CL activation energy (AE) imaging is used to study changes in the AE for the thermal quenching of the luminescence in close proximity to the microcracks, and correlations are obtained with changes in the QD excitonic transition energy and changes in the average AlN band edge energies relative to the ground electron and hole states in the QD. Localized CL spectroscopy of the QDs exhibits emissions from both the ground and excited states, whose relative contributions depend on the level of excitation and temperature. Experimental results indicate that the polarization anisotropy vanishes at high temperatures (∼300 K) with an increasing excitation of the QDs, while the anisotropy decreases more slowly with excitation at low temperatures (∼60 K). A theoretical modeling of the effect of carrier filling on the polarization anisotropy and the excitonic transition energy was performed, as based on three-dimensional self-consistent solutions of the Schrödinger and Poisson equations using the 6×6 k⋅p and effective mass methods for the calculation of the e-h wave functions. The authors attribute carrier filling and a thermal excitation of holes into higher energy QD hole states during excitation to account for the observed gradual decrease in the polarization anisotropy with an increasing electron-hole pair excitation density at T=300 K.